Unknown script signs from the Urartian Tomb of Yerevan - Badalyan, Mikayel (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The Urartian (Biainian) tomb of Yerevan is situated in the capital city of the Republic of Armenia, within the area now occupied by “Yerevan Mall”. Discovered in 1984 during construction activities, it has since been the subject of detailed archaeological investigation. Although several comprehensive studies have been devoted to the monument, none have addressed the engraved symbols found on one of the façade stones near the entrance and on two tuff fragments uncovered in close proximity to the façade. Architecturally, the Yerevan tomb shows close affinities with Urartian funerary monuments from Altıntepe and with a recently discovered structure of similar type in the village of Gökçayır near Alashkert (modern Türkiye). It is noteworthy that one of the Altıntepe tombs contained a metal funerary urn inscribed with a Luwian hieroglyphic text. Երևանի ուրարտական (բիայնական) դամբարանը գտնվում է Հայաստանի Հանրապետության մայրաքաղաք Երևանում՝ ներկայիս «Երևան Մոլլի» տարածքում: Այն 1984 թ․ բացվել է շինարարական աշխատանքների ժամանակ, այնուհետև ենթարկվել է մանրամասն ուսումնասիրության: Չնայած դամբարանի վերաբերյալ առկա են մի քանի համապարփակ աշխատություններ, սակայն դրանցում չկա անդրադարձ դամբարանի մուտքի ճակատային հատվածի քարերից մեկին և նույն ճակատային հատվածի դիմաց հայտնաբերված տուֆե երկու քարաբեկորներին արված անհայտ գրային նշաններին: Урартская (Биайнская) гробница в Ереване – столице Республики Армения, находится на территории современного торгового центра «Ереван Молл». Она была обнаружена в 1984 году при проведении строительных работ. Несмотря на наличие нескольких фундаментальных трудов, посвящённых исследованию данного памятника, до настоящего времени вне поля внимания ученых остались знаки, высеченные на одном из фасадных камней у входа и на двух туфовых фрагментах, найденных перед фасадом. В статье нами выделено 12 знаков, выявленных на фасадном камне и фрагментах из ереванской гробницы; два из них, по всей вероятности, повторяются, что позволяет предположить существование определённой письменной системы. Большинство знаков состоят из вертикальных и горизонтальных линий, точек и фигур в форме «>» и «<», схожих с элементами ахеменидской клинописи.
Keywords: History